Dairy production analysis and its accounting and information support (on the example of the Orenburg region) - L.G. Egorova (Интеллект. Инновации. Инвестиции, 2020)
The relevance of the research based on the fact that the agro-industrial complex of processing enterprises activity has a crucial importance not only for the development of regional economy and economy of the whole Russia but also the social importance in providing the population of the country with high quality food. So the milk products are included in the consumer basket for all the socio-demographic groups of the population. Because of this the research of milk processing enterprise activity is actualized. The main aimof the article is to give an estimation to the modern state of the dairy industry in context of Orenburg region and promising areas of its development, to work out recommendations which will help to extend boundaries of accounting informative value for making well-timed and effective decisions in running the milk enterprises activity and to determine at the same time the main directions of increasing the milk processing enterprises efficiency and improving its accounting and information support. The following set of basic research methods (observation, grouping, comparison, analysis, logical generalization), and also elements of accounting – documentation, the system of accounts were used in the work. The results of the given analyses of milk production and milk processing products in Orenburg region in comparison with the other regions of Russia were described in the article. Development trends of the milk products market were identified under the conditions of import substitution and economic sanctions. Factors and the way they influence on the development of the given economic branch in the researching region and all the country were classified. Methodological recommendations for identification and grouping raw material and milk processing products in the modern accounting were worked out. Basic principles of documentation and operating control for the used raw material safety and quality of the milk produced products were proved. The results of the research have as theoretical as practical spheres of application. They can be used in diary enterprises and industry management and also recommended as scientific and analytical discipline in educational process of the universities. It was made a conclusion that there are plenty factors which influence on the development of milk processing enterprises of Orenburg region. Only after ranging of those factors it was possible to prove the main ways of development for the given industry in the researching region and find out the accounting role and importance as a management function in diary brunch of economy.